Therapeutic Angiogenesis in Ischemic Heart Disease - Helisch, Armin; Anthony Ware, J. (Thrombosis and Haemostasis, 1999)
Coronary heart disease is the leading cause of death in the Western world. Traditionally, patients with coronary heart disease requiring a revascularizing procedure have had to undergo either coronary artery bypass surgery, which usually involves open thoracotomy, or percutaneous transluminal balloon angioplasty, or a related procedure. Unfortunately, especially in patients with severe diffuse coronary heart disease, revascularization by these means can be difficult or even impossible. It has been shown that incomplete revascularization is a predictor of a worsened postoperative outcome (i.e., recurrent angina, myocardial infarction, or even death).We have known for a long time that many patients with ischemic disease develop angiographically visible collateral vessels. Initial research focused on the enlargement of preexisting collateral vessels, a process for which Wolfgang Schaper has proposed the term “neoarteriogenesis.”1 It is now clear that true “angiogenesis,” defined as the formation of new vessels by sprouting from preexisting vessels, also occurs. The latter also should be differentiated from the earliest embryological process of new vessel formation directly from mesodermal endothelial cell precursors, which is called “vasculogenesis.”2In the last few years, clinical trials have been initiated with the goal of enhancing angiogenesis to treat peripheral vascular disease and ischemic heart disease. In this review, we will summarize the underlying concepts for this novel mode of therapy, plus the available information on its efficacy.The sprouting of capillaries from preexisting vessels (angiogenesis) is a normal and necessary process to supply the growing organism with nutrients and oxygen. Ischemic vascular disease, along with wound healing and the monthly endometrial proliferation, are conditions in which angiogenesis may be beneficial or necessary. Of course, angiogenesis is also part of the pathogenic mechanism of tumors, hemangiomas, proliferative retinopathies, and inflammatory diseases like rheumatoid arthritis and psoriasis.3 Even in ischemic vascular disease, it is possible that vascularization of atherosclerotic plaques by vessels arising from the vasa vasorum leads to hemorrhages with consequent plaque instability,4 and thus enhancing angiogenesis may promote vessel pathology.The vasculature of a 70 kg adult is lined by approximately 1,000 m2 of quiescent endothelial cells with a very low turnover rate that can exceed 1,000 days.3 Upon angiogenic activation (e.g., by growth factors released during ischemia), a local inflammatory reaction often can be observed with increased local vascular permeability, vasodilation, and accumulation of monocytes and macrophages. These latter cells release more cytokines and growth factors, which lead to the accumulation of additional inflammatory cells. They also release enzymes that promote the proteolytic degradation of the underlying extracellular matrix and basal membrane. Such degradation causes the endothelial cells to detach from their neighboring cells and the underlying matrix, followed by chemotactic migration and proliferation. Subsequently, formation of a lumen occurs and, eventually, maturation and growth of the newly formed vessel.2,5,6 In vessels larger than capillaries, vascular smooth muscle cells proliferate and migrate as well. In addition, it recently has been shown that circulating endothelial cell precursors released from the bone marrow participate in the formation of new vessels in the setting of tissue ischemia.7 Investigators currently are assessing the importance and contribution of the latter mechanism to neovascularization in the adult organism. If it proves substantial, the traditional means of differentiating between angiogenesis and vasculogenesis may need to be reconsidered.The regulatory mechanisms of angiogenesis are very complex and only partially understood. Both mechanical factors and multiple endogenous inhibitors have been identified that probably act to inhibit inappropriate endothelial cell proliferation following mitogenic stimulation.3 Most of the known angiogenesis inhibitors circulate in the blood and some have been detected in the matrix around endothelial cells. They include platelet factor 4, thrombospondin-1 and -2, tissue inhibitors of metalloproteinases, and interferon α.3,8 It is unclear whether the endothelium specific inhibitors angiostatin, a 38 kDa fragment of plasminogen,3 and endostatin, a 20 kDa fragment of collagen XVIII,9 are present in physiologically active amounts in organisms without malignant tumors. Of potential importance for myocardial angiogenesis is the recent isolation of an 11 kDa inhibitor of endothelial and smooth muscle proliferation and angiogenesis with homology to the B-cell translocator gene (btg-1) from the bovine heart.1,10 Regarding mechanical factors, contact inhibition of endothelial cell proliferation, which easily can be observed by growing primary endothelial cells in a culture dish, limits excessive endothelial cell growth. Additionally, endothelial cells are surrounded in vivo by a basal lamina, which creates a physical barrier between endothelial cells and the extravascular space. Pericytes may regulate or restrain endothelial cell proliferation. Angiogenesis also can be inhibited by sequestration of angiogenic factors in the extracellular matrix; furthermore, changes of endothelial cell shape may decrease their sensitivity to growth factors.3 On the other hand, many endogenous factors that promote angiogenesis have been identified. These include various growth factors that interact with receptor tyrosine kinases (see below), angiogenin, granulocyte colony stimulating factor, interleukin-8, and proliferin.3,11,12 The balance of these inhibitory and mitogenic influences determines whether angiogenesis occurs.